2021
DOI: 10.1177/07356331211030847
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Three Group-Level Metacognitive Scaffoldings on In-Service Teachers’ Knowledge Building

Abstract: Group-level metacognitive scaffolding is critical for productive knowledge building. However, previous research mainly focuses on the individual-level metacognitive scaffoldings in helping learners improve knowledge building, and little effort has been made to develop group-level metacognitive scaffolding (GMS) for knowledge building. This research designed three group-level metacognitive scaffoldings of general, task-oriented, and idea-oriented scaffoldings to facilitate in-service teachers’ knowledge buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The possible reason is that the self‐planning and self‐evaluation mechanisms effectively activated the students' planning and evaluation awareness. This result aligns with previous research, which indicated that appropriate metacognitive scaffolding could stimulate students' metacognition (Ouyang et al, 2022). However, in terms of knowledge of cognition and monitoring, there were no statistically significant differences between the two groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The possible reason is that the self‐planning and self‐evaluation mechanisms effectively activated the students' planning and evaluation awareness. This result aligns with previous research, which indicated that appropriate metacognitive scaffolding could stimulate students' metacognition (Ouyang et al, 2022). However, in terms of knowledge of cognition and monitoring, there were no statistically significant differences between the two groups.…”
Section: Discussionsupporting
confidence: 92%
“…It has been found that self‐reflection can improve students' ability to regulate and thus improve their problem‐solving skills (Panaoura, 2012). In addition, developing a learning plan, monitoring the learning process, evaluating and reflecting can stimulate students' metacognition (Ouyang et al, 2022), which is significantly positively related to computational thinking (Şen, 2022) and therefore contributes to improving students' computational thinking (Liu et al, 2021; Liu & Liu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Reflection can also create knowledge about one's cognition and regulate cognition (Simons, 1994). Developing a learning plan, monitoring the collaborative learning process, and engaging in assessment and reflection can activate metacognition (Kim & Lim, 2018; Ouyang et al, 2022). The shared regulation collaborative programming approach provides scaffolding to students regarding the problem at hand, facilitating group planning, monitoring, and reflection.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolding involves providing temporary support to learners, enabling them to accomplish tasks that would be challenging without assistance. In the realm of language learning, Ouyang et al (2022) suggest that scaffolding can take various forms, including providing additional resources, offering hints or prompts, and structuring collaborative activities. Scaffolding aligns with the communal values deeply ingrained in Nepalese society, where collaboration and shared responsibility are highly valued.…”
Section: The Zpd: Application In Local Contextmentioning
confidence: 99%